2019
DOI: 10.1080/20002297.2019.1603524
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro and in vivo study of plasma treatment effects on oral biofilms

Abstract: Management of dental plaque/biofilms is critical to maintain oral health. The objective of this study is to investigate the treatment effects of non-thermal atmospheric gas plasmas on oral biofilm formation and recovery under in vitro and in vivo conditions. Streptococcus mutans biofilms, a significant contributor to tooth decay, were cultured and treated by plasma. It was found that plasma treatment not only significantly reduced the in vitro biofilms, but also increased the metabolic activity of the bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
0
11
0
2
Order By: Relevance
“…In terms of a caries preventive therapy, Sprague-Dawley rats were treated with CAP for 2 min on the molars of one side, the other side served as control. After six months the caries rate on the test side was decreased by 20% compared to the control [ 29 ]. Another possible clinical application could be the disinfection of the cavity after caries excavation.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of a caries preventive therapy, Sprague-Dawley rats were treated with CAP for 2 min on the molars of one side, the other side served as control. After six months the caries rate on the test side was decreased by 20% compared to the control [ 29 ]. Another possible clinical application could be the disinfection of the cavity after caries excavation.…”
Section: Discussionmentioning
confidence: 99%
“…It is documented that the use of nonthermal plasma does not involve harmful chemical substances and it seems to be an interesting technique of cleaning the surface of membranes used in wastewater treatment. Moreover, the results demonstrated by Hong et al showed that plasma treatment not only inactivates the biofilm but also inhibits biofilm re-growth after surgery [67]. The authors re-cultured plasma-treated biofilms of Streptococcus mutans and observed interesting changes in the physiological activity of these bacteria.…”
Section: Resultsmentioning
confidence: 98%
“…The differences can be observed, for example, in the cultivation time period, the initial density of bacterial suspensions, static versus shaking mode of cultivation, the substrate for initial bacterial attachment, and predominantly in the choice of cultivation media [18][19][20]. For staphylococcal biofilm formation, media such as Mueller-Hinton broth [21], brain heart infusion [22], minimal growth media and tryptic soy broth are often used [23,24]. For the enhancement of staphylococcal biofilm biomass formation in vitro, various media supplements (glucose, NaCl, HP, citrate, etc.)…”
Section: Inconsistency In Methodical Approaches and Differences In Cultivation Conditions For Biofilm Formation Can Lead To Discrepanciesmentioning
confidence: 99%